Ṣūfī Networks and Urban Transformation in Sudan through Education and Social Integration - Ahmad Nabilul Maram; Muhammad Fuyudun Niam Imam; Imam Ghazali Said; Ahmad Busyairi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Challenging conventional narratives of militarized Islamic expansion, this study investigates the instrumental role of Ṣūfī institutions in Sudan's peaceful and integrative Islamization. It establishes the significance of these institutions not merely as spiritual centers but as foundational frameworks for social cohesion and community resilience, particularly in response to contemporary crises. Focusing on the peaceful spread of Islam, the research examines how Ṣūfī orders utilized non-coercive mechanisms, including migration, trade, and spiritual mediation, to embed Islamic practices within syncretic societies. Employing institutional ethnography, the methodology reveals the socio-political functions of Ṣūfī centers such as the Masīd and Khalwa. Results demonstrate that these institutions transcended doctrinal roles, becoming engines of urbanization, de-tribalization, and grassroots governance. The research particularly emphasizes the educational, conflict-resolution, and humanitarian contributions of Ṣūfī networks, especially during crises like the April 15, 2023, war. Case studies highlight how spiritual leaders provided shelter, healthcare, and psychological support, reinforcing the Masīd as a moral and communal nucleus. This integrative role underscores the adaptability of Ṣūfīsm in responding to changing social dynamics, offering an enduring model of inclusive governance and interethnic solidarity. The findings contribute to academic discussions on religion and social order, illustrating how faith-based institutions can serve as resilient frameworks for community development in fragile states.